Residential segregation and socio-spatial processes in Marseille. Urban social sustainability challenge - Grzegorczyk, Anna (Bulletin of Geography. Socio-economic Series, 2021)
The aim of the study is to determine the scale and patterns of the demographic, social and ethnic segregation of Marseille and its metropolitan area, in the light of the socio-spatial processes it is currently undergoing and its influence on social sustainability. In the study, multidimensional quantitative method combined with qualitative field observations are used to determine the current hierarchy of population groups subject to residential segregation and a mechanism of segregation development. The mechanism is revealed by indicating the role of gentrification uniqueness, spread of enclaves of wealth and permanence of enclaves of poverty, which are all conditioned in Marseille by city’s economic restructuring, liberal housing policy and historical role of immigrants.